Dual Function pH Responsive Bispecific Antibodies for Tumor Targeting and Antigen Depletion in Plasma - Bogen, Jan P.; Hinz, Steffen C.; Grzeschik, Julius; Ebenig, Aileen; Krah, Simon; Zielonka, Stefan; Kolmar, Harald (Frontiers in Immunology, 2019)
Shedding of membrane‐bound cell surface proteins, where the extracellular domain is released and found in the circulation is a common phenomenon. A prominent example is CEACAM5 (CEA, CD66e), where the shed domain plays a pivotal role in tumor progression and metastasis. For treatment of solid tumors, the presence of the tumor-specific antigen in the plasma can be problematic since tumor-specific antibodies might be intercepted by the soluble antigen before invading their desired tumor target area. To overcome this problem, we developed a generic procedure to generate bispecific antibodies, where one arm binds the antigen in a pH-dependent manner thereby enhancing antigen clearance upon endosomal uptake, while the other arm is able to target tumor cells pH-independent. This was achieved by incorporating pH-sensitive binding modalities in the common light chain IGKV3-15*01 of a CEACAM5 binding heavy chain only antibody. Screening of a histidine-doped light chain library using yeast surface display enabled the isolation of pH-dependent binders. When such a light chain was utilized as a common light chain in a bispecific antibody format, only the respective heavy/light chain combination, identified during selections, displayed pH-responsive binding. In addition, we found that the altered common light chain does not negatively impact the affinity of other heavy chain only binders towards their respective antigen. Our strategy may open new avenues for the generation of bispecifics, where one arm efficiently removes a shed antigen from the circulation while the other arm targets a tumor marker in a pH-independent manner.